Evaluation Of Education And Economic Barriers In Implementing Essential Medicines Concept In Malaysia - Ahmed, Hind Mahjowb Abdallah (2009)
Although the National Essential Medicines List (NEML) in Malaysia was launched in 2000, there were no studies conducted to measure prescribers, pharmacists and medical and pharmacy students’ awareness on essential medicines concept, or to measure affordability of actual prescriptions used for treatment of chronic conditions. Walaupun senarai Ubat Perlu Kebangsaan (NEML) di Malaysia telah dilancarkan pada tahun 2000, tidak terdapat sebarang kajian yang telah dijalankan untuk mengukur tahap kesedaran terhadap konsep ubat perlu di kalangan pengamal perubatan, ahli farmasi dan pelajar-pelajar perubatan dan farmasi, atau untuk mengukur tahap keupayaan membeli ubat untuk rawatan penyakit kronik.